Linguistic Features as Depicted in Tulembang Mantra - Badaruddin, M S (KnE Social Sciences, 2018)
Tulembang Mantra is the oldest form of literature in South Sulawesi as an aspect of ancient cultures which is still maintained up to the present time and is still used by the traditional community such as farmers. The traditional community of Makassar uses it according to its purpose. Tulembang Mantra is the form of expressions or words believed to be able to provide occult power. The power aims to give strength to human beings in carrying out various activities. The research used the recording, interview and note taking to collect the data. The population consisted of five mantras and three informants. The samples were the same as the population. The data were analyzed using the qualitative descriptive method [3]. The research result indicates that the form is a kind of praises to something occult or something that must be assumed sacred. Tulembang Mantra exerts Basmallah “in the name of Allah” and Assalamu’alaikum “peace be upon you” in general as an opening discourse. The form of discourse is more as monolog and dialog. They are used to talk to the Almighty God and ”paddy ”. As the result, mantra tends to be free in choosing the syllables, lyrics, or rhyme. “This is clear that the mantra contains acknowledgement, hope, self-cleanliness and mind, serenity, and inner satisfaction”. Keywords: tulembang mantra, features, occult power, textual meaning, sacred